ICT Based Informal Learning Approach for Semi Literate and Illiterate Peoples in Rural Area of Bangladesh - Akther, Farzana (Proceedings of the International Conference on Networked Learning, 2010)
The rural areas of Bangladesh are inhabited by several semi literate and illiterate people. Furthermore, it is an enormous challenge to enhance the basic education, literacy and livelihood of rural people. It is worldwide expected that Information and Communication Technology (ICT) can provide real value of life to such populations through ICT development within different information domains. GrameenPhone Community Information Centers (GPCICs) in Bangladesh have been initiated with the aim of bringing the benefits of new technologies providing information of different domains to the rural area people. This offers an opportunity to build up social networks among the rural peoples and GPCICs can thus constitute potential informal learning centers in the form of networked ICTs. In order to be used, the Community Information Centers require their users to have certain literacy skills. In rural areas, marginalized/ disadvantaged people in developing countries often lack these skills and therefore they are not able to fully benefit from ICT. The lack of literacy skills is often considered to be at the heart of this problem. Another way to approach this problem is to determine how the technology can be ready for this specific semi literate and illiterate user group - in other words - developing ICTs that can easily be used without such skills. In this context, the aim of my study is to explore an improved understanding of how semi literate and illiterate people can access information through ICT. I will also investigate how ICT-based informal learning can empower the rural semi literate and illiterate peoples. The aims, objectives and research problems of my study will be addressed through a multi methodological approach that combines an ethnographic research and an action research approach. Here, the ethnographic research method will be used to process new understanding of ICT for semi literate and illiterate people and the action research method will be used as a framework for my research project that will link to the plans and activities of the project as well as assist in bringing new activities through new understandings of situations. The Social learning theory Communities of practice (CoP) is considered as a theoretical framework to create ICT-based informal learning environment for low literate people which can build a sustainable ICT development. The goal of this research is to develop a guideline for ICT-based informal learning projects designed especially for low literacy people in rural areas and this guideline will explore the environments, technologies and requirements for ICT to support rural development.